2023
DOI: 10.3390/diagnostics13030457
|View full text |Cite
|
Sign up to set email alerts
|

VIS-NIR Diffuse Reflectance Spectroscopy System with Self-Calibrating Fiber-Optic Probe: Study of Perturbation Resistance

Abstract: We report on the comparative analysis of self-calibrating and single-slope diffuse reflectance spectroscopy in resistance to different measurement perturbations. We developed an experimental setup for diffuse reflectance spectroscopy (DRS) in a wide VIS-NIR range with a fiber-optic probe equipped with two source and two detection fibers capable of providing measurements employing both single- and dual-slope (self-calibrating) approaches. In order to fit the dynamic range of a spectrometer in the wavelength ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…At the onset of the arterial occlusion, a motion artifact that lasts approximately 1 to 2 s is noticeable at both wavelengths for all data types. This artifact is also visible in DS data types, even though they should be largely insensitive to changes in the optical coupling between sources and detectors 16 , 31 . A possible reason for this artifact to appear in DS data is that the optical coupling change may have occurred faster than the data sampling cycle through all sources and detectors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the onset of the arterial occlusion, a motion artifact that lasts approximately 1 to 2 s is noticeable at both wavelengths for all data types. This artifact is also visible in DS data types, even though they should be largely insensitive to changes in the optical coupling between sources and detectors 16 , 31 . A possible reason for this artifact to appear in DS data is that the optical coupling change may have occurred faster than the data sampling cycle through all sources and detectors.…”
Section: Resultsmentioning
confidence: 99%
“…This artifact is also visible in DS data types, even though they should be largely insensitive to changes in the optical coupling between sources and detectors. 16 , 31 A possible reason for this artifact to appear in DS data is that the optical coupling change may have occurred faster than the data sampling cycle through all sources and detectors. No motion artifact is visible at the onset of the venous occlusion [ Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies were devoted to the use of diffuse reflectance spectroscopy (DRS). V. Perekatova et al reported on the comparative study of self-calibrating and single-slope DRS in terms of stability against various measurement disturbances [26]. The authors designed an experimental setup for DRS in a wide spectral range (from VIS to NIR), including a fiber-optic probe with two fibers for delivery and two used to receive light.…”
mentioning
confidence: 99%